Livelihood Diversification Strategies to Climate Change among Smallholder Farmers in Northern Ghana - Asravor, R.K. (Journal of International Development, 2018)
Employing the Margalef index of diversification, the linear regression model and three‐step feasible generalised least square, we analyse the impact of climate variability and expectation on the diversification strategies and vulnerabilities of rural households in Northern Ghana. The finding indicates households have diversified on and off the farm. The decrease average rainfall increases the diversification of total labour and female labour supply whilst decreasing diversification of cropland and income. Higher average rainfall lowers mean and variable per capita consumption. Extension service is an effective policy variable under high climate variability. We recommend increasing extension services and women economic empowerment. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: Margalef index; Three-step feasible generalised least squares; Climate change; Livelihood; Diversification